PANDANACEAE OF SUMBAWA, WEST NUSA TENGGARA, INDONESIA - ARY PRIHARDHYANTO KEIM; MULYATI RAHAYU (Reinwardtia, 2010)
KEIM, A. P. & RAHAYU, M. 2010. Pandanaceae of Sumbawa, West Nusa Tenggara, Indonesia. Reinwardtia 13(2): 151-158. - Two species of Freycinetia and two species of Pandanus are recorded from the Batulanteh vicinity in West Sumbawa. One species is a new species described here for the first time and named Freycinetia sumbawaensis A.P. Keim & M. Rahayu.